Disordered Eating Behaviors, Perceived Stress and Insomnia During Academic Exams: A Study Among University Students - Elena-Gabriela Strete; Mădălina-Gabriela Cincu; Andreea Sălcudean (Medicina)
Background and Objectives: During exam sessions, many students experience high levels of stress caused by the large volume of material to study, tight deadlines, and pressure to achieve top grades. This study aimed to examine the relationship between academic stress, sleep disturbances, and eating behaviors by using validated questionnaires administered to a student sample. As stress levels increased, the data revealed a higher frequency of insomnia symptoms and disordered eating, including behaviors such as compulsive eating and irregular meal patterns. Materials and Methods: This cross-sectional, correlational study was conducted on a convenience sample of 317 university students from various academic centers across Romania. Participants were recruited via online distribution of a self-administered questionnaire during a four-month period, including exam sessions. The survey included the Perceived Stress Scale (PSS), the Insomnia Severity Index (ISI), and the Eating Disorder Examination Questionnaire (EDE-Q), alongside additional items assessing perceived links between stress, sleep, and eating behaviors, and the use of medication. Data were analyzed using SPSS with Spearman correlations, t-tests, and linear regression. Results: Statistical analyses revealed significant and positive associations between perceived stress levels and insomnia, as indicated by Spearman’s correlation (p < 0.01). A similar significant correlation was identified between perceived stress and disordered eating behaviors among students. Specifically, the feeling of being overwhelmed by academic workload showed a strong positive correlation with a lack of control over eating behaviors (r = 0.568). Furthermore, linear regression analysis confirmed a significant predictive relationship between feeling overwhelmed and the tendency to eat excessively beyond initial intentions, with a standardized regression coefficient B = 0.581 (p < 0.001). A separate regression analysis focusing on exam-related stress and episodes of compulsive eating behavior demonstrated a comparable result (B = 0.573, p < 0.001), indicating a robust positive association. Additionally, independent samples t-tests demonstrated that students experiencing high levels of stress during the exam period reported significantly greater difficulties with sleep initiation and higher levels of disordered eating compared to their peers with lower stress levels. The difference in insomnia scores was highly significant (t = 11.516, p < 0.001), as was the difference in eating behavior scores (t = 10.931, p < 0.001). Conclusions: These findings underscore the need for emotional support services and effective stress management strategies, enabling students to navigate academic demands without compromising their mental or physical well-being.